Open hole quasi-static and fatigue characterisation of 3D woven composites. (1st November 2015) - Dai, S.; Cunningham, P.R.; Marshall, S.; Silva, C.
Abstract: This paper presents a comprehensive study on the open-hole quasi-static tensile and tension–tension fatigue behaviour of an orthogonal and an angle-interlock 3D woven carbon/epoxy composite. The full-field strain distribution during quasi-static tests was characterised using digital image correlation (DIC), and the fatigue damage behaviour was monitored using an infra-red camera. The notched tensile strength was less than 17% lower than the un-notched tensile strength and not very sensitive to the notch size. The fatigue specimens were loaded with maximum stress of about 60% of the ultimate failure stress and no complete fracture occurred after 5, 000, 000 cycles. The residual fatigue strength was also found to be similar to the quasi-static tensile strength in both weaves. The surface crack initiation and progression during fatigue loading was identified using thermoelastic stress analysis which revealed that the orthogonal weave had larger surface damage area than the angle-interlock weave.